2005
DOI: 10.1002/hbm.20197
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor organization in double cortex syndrome

Abstract: Subcortical band heterotopia is a diffuse malformation of cortical development related to pharmacologically intractable epilepsy. On magnetic resonance imaging (MRI), patients with "double cortex" syndrome (DCS) present with a band of heterotopic gray matter separated from the overlying cortex by a layer of white matter. The function and connectivity of the subcortical heterotopic band in humans is only partially understood. We studied six DCS patients with bilateral subcortical band heterotopias and six healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 60 publications
5
11
0
4
Order By: Relevance
“…Given the profoundly abnormal cortical morphology in our patients, it is surprising to find intact visual function and organization within PMG, and this suggests either a considerable redundancy in cortical visual circuitry or a significant plasticity of the polymicrogyric cortex involved in the processing of visual inputs. These findings are in line with our previous observation in patients with subcortical band heteropia showing that the abnormally layered subcortical band may sustain normal sensorimotor function [Jirsch et al, 2006]. While visual organization remains intact in our PMG patients, it is less clear whether these grossly abnormal occipital areas are involved in the genesis of these patients' seizures as intracranial EEG studies were not performed.…”
Section: Functional and Morphological Properties Of Pmgsupporting
confidence: 92%
“…Given the profoundly abnormal cortical morphology in our patients, it is surprising to find intact visual function and organization within PMG, and this suggests either a considerable redundancy in cortical visual circuitry or a significant plasticity of the polymicrogyric cortex involved in the processing of visual inputs. These findings are in line with our previous observation in patients with subcortical band heteropia showing that the abnormally layered subcortical band may sustain normal sensorimotor function [Jirsch et al, 2006]. While visual organization remains intact in our PMG patients, it is less clear whether these grossly abnormal occipital areas are involved in the genesis of these patients' seizures as intracranial EEG studies were not performed.…”
Section: Functional and Morphological Properties Of Pmgsupporting
confidence: 92%
“…To date, the most extensive fMRI study, by Janszky et al, included 28 patients with MCD, among them 4 with subcortical heterotopia, 4 with subependymal or periventricular heterotopic nodules, 9 with polymicrogyria, and 8 with focal cortical dysplasia 13 . Additionally, Speer et al and Jirsch et al reported on a total of 9 patients with band heterotopia 15,19 …”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that there were two types of neuron populations in BHT: one that followed a normal pat- tern for migration and the other that did not reach the cortex but remained stranded in subcortical white matter because of failure of microtubule function due to the X-linked mutation [10,16]. (3) Regional specificity [18] may mainly account for these differences, as the different regions of interest (ROIs) were focused in these two studies. Due to the severe deficits of neurons in the outer cortex, the fibers stemming from them were stunted, sparse, and fragmentary (Figure 2a), and thus they could not traverse the heterotopic gray matter.…”
Section: Discussionmentioning
confidence: 99%